The Gut-Lung Axis in Health and Respiratory Diseases: A Place for Inter-Organ and Inter-Kingdom Crosstalks - Enaud, Raphaël; Prevel, Renaud; Ciarlo, Eleonora; Beaufils, Fabien; Wieërs, Gregoire; Guery, Benoit; Delhaes, Laurence (Frontiers in Cellular and Infection Microbiology, 2020)
Gut and lungs are anatomically distinct, but potential anatomic communications and complex pathways involving their respective microbiota have reinforced the existence of a gut-lung axis (GLA). Compared to the better-studied gut microbiota, the lung microbiota, only considered in recent years, represents a more discreet part of the whole microbiota associated to human host. While the vast majority of studies focused on the bacterial component of the microbiota in healthy and pathological conditions, recent works have highlighted the contribution of fungal and viral kingdoms in both digestive and respiratory levels. Moreover, growing evidences indicate the key role of inter-kingdom crosstalks in maintaining host homeostasis and in diseases evolution. In fact, the recently emerged GLA concept involves host-microbe as well as microbe-microbe interactions, based both on localized and long-reaching effects. GLA can shape immune responses and interfere with the course of respiratory diseases. In this review, we aim to analyse how the lung and gut microbiota influence each other and may impact on respiratory diseases. Due to the limited knowledge on the human virobiota, we focused on gut and lung bacteriobiota and mycobiota, with a specific attention on inter-kingdom microbial crosstalks which are able to shape local or long-reached host responses within the GLA.